An Introductory Review - Computer Applications In Pyrometallurgical Processes: The-State-Of-The-Art - Harrison R. Cooper (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Computer process analysis and control techniques are overcoming major hurdles to acceptance in the mineral industry. With the growing list of new advances characteristic of a rapidly maturing discipline, management of the companies on the leading edge are keenly aware of the advantages of using computer methods in process applications. Significant advancement is already evident in such technical areas as operations research, mathematical modeling, statistical methods, and computer-based procedural techniques. The early advances during the past decade are already documented in prior symposium proceedings of this series. Thus, the currently active areas of the advancing technology are emphasized here. This section deals with applications in pyrometallurgical and kiln processes. The two sections which follow deal with concentrating operations from two points of view: 1) mathematical modeling, and 2) on-line control. In the metallurgical field, emphasis on developing effective process computer applications for the steel industry began in the late 1950's. Simulation techniques also received substantial attention. The steel industry was soon joined by the cement industry in the development of computer methods for process applications. Computers were in use for feed-material blending and kiln control in the early 1960's. Computer development in other pyro processes, such as aluminum reduction and glass-making, also marked significant advances by the mid 1960's. Aluminum smelter potline control is a nearly universal application at this point, and the development of glass furnace computer process control represented a recent important technical advance in digital control techniques. Steel Hot strip rolling was the earliest significant process computer application in the metallurgical industry. Computer control of rolling mill operations is now a steel mill standard component, particularly in plants newly placed into production. 1, 2 Initial computer installations principally carried out procedural routines in setting mill clearances for production lot control. Recent developments are leading toward feedback control based on mathematical model techniques. 3